Polyphenols extracted from Enteromorpha clathrata alleviates inflammation in lipopolysaccharide-induced RAW 264.7 cells by inhibiting the MAPKs/NF-κB signaling pathways. (25th March 2022) - Huang, Ping; Hong, Jingxia; Mi, Jie; Sun, Bolun; Zhang, Jinjie; Li, Chao; Yang, Wenge
Abstract: Ethnopharmacology relevance: Enteromorpha has long been recorded in traditional Chinese medicine, with cholesterol-lowering, anti-cancer, anti-inflammatory and antibacterial effects. Recently, we extracted the polyphenol-enriched fraction from Enteromorpha clathrata ( E. clathrata ) by ethyl acetate (ECPs), and isolated six individual polyphenols from ECPs via high-speed counter-current chromatography (HSCCC) with high-performance liquid chromatography (HPLC). Aim of the study: In this study, we explored the anti-inflammatory activity and underlying mechanism of ECPs in lipopolysaccharide (LPS)-induced RAW 264.7 macrophages. Materials and methods: ECPs and the six polyphenols were used for nitric oxide (NO) assay to identify the components with potent inflammation inhibitory effect. Enzyme-linked immunosorbent assay (ELISA), quantitative real-time PCR (qPCR), flow cytometry, and Western blot analysis were applied to further investigate their anti-inflammatory effects and underlying mechanism in LPS-stimulated RAW264.7 cells. Results: ECPs and the three individual polyphenols, including (−)-epicatechin, epigallocatechin-3- O -gallate and (−)-epicatechin-3- O -gallate, showed in vitro immunosuppressive activity by altering the cell biology at the gene, protein and functional levels in a dose- and species-dependent manner. Their anti-inflammatory effects were achieved by inhibiting LPS-induced production of nitric oxide and its upstream enzyme inducible nitric oxide synthase (iNOS), the pro-inflammatory cytokines including interleukin-1 beta (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α), as well as the phagocytotic capacity, without cytotoxicity. The mechanism study further revealed that these anti-inflammatory properties were, at least partly, attributed to the suppressed activation of nuclear factor-κB (NF-κB) and p38 mitogen-activated protein kinase (MAPK) signaling pathways. Conclusions: These findings indicated for the first time the correlation between the anti-inflammatory activity of ECPs and NF-κB and MAPK signaling pathways, suggesting that polyphenol-enriched organic fraction of E. clathrata could be potential candidate as therapeutic agent for treating inflammatory diseases. Graphical abstract: Image 1 Highlights: E. clathrate polyphenols exhibited potent anti-inflammatory activity in vitro . E. clathrate polyphenols modulated mRNA and protein levels of inflammatory mediators. E. clathrate polyphenols inhibited p38 MAPK and NF-κB signaling pathways.